Lenjeh, Gittal, Kanyi dll: Kata-Kata Lokal untuk Mengontrol dan Menekan Ekspresi Tubuh Perempuan - Listiorini, Dina; Vidiadari, Irene Santika (Jurnal Komunikasi, 2024)
This article discusses the existence of the term "flirtatious" in various regions of Indonesia on women's behavior, particularly in public spaces, reflecting symbolic power dynamics. Employing a qualitative phenomenological approach with FGDs and in-depth interviews involving individuals from diverse backgrounds, cultures, and occupations, it explores how these local expressions regulate women's conduct. Using Bourdieu's theory about symbolic violence, the findings reveal that such terms primarily target women to modify their behavior and are enforced by authoritative figures, shaping girls' interactions with men beyond the family sphere. These local expressions evolve into entrenched beliefs and practices, representing not only familial norms but also perpetuating symbolic violence within Indonesia's patriarchal cultural framework